2017
DOI: 10.1002/ijgo.12360
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of combined cabergoline and coasting in preventing ovarian hyperstimulation syndrome during in vitro fertilization/intracytoplasmic sperm injection cycles

Abstract: Combining coasting and cabergoline was associated with a lower OHSS rate compared with either therapy alone. CLINICALTRIALS.GOV: NCT01984320.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A total of 425 articles were initially identified. After by layer screening, only 5 [14] [18] studies met criteria, including 421 women. Document screening process and results shown in Figure 1.…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 425 articles were initially identified. After by layer screening, only 5 [14] [18] studies met criteria, including 421 women. Document screening process and results shown in Figure 1.…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
“…Subgroup analysis result showed that 0.5 mg cabergoline daily was obviously increased fertilization rate and the abortion rate was significantly lower than coasting group. One study proved that the combined administration provided better protection without notable side effects [18]. However, Hwang [19] pointed out that the efficacy of cabergoline is not good in preventing severe OHSS through two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that vaginal administration of bromocriptine could reduce the probability of adverse reactions in the digestive tract and nervous system, and has a preventive effect on OHSS (15). Bromocriptine as dopamine receptor agonists is currently often used for the OHSS prevention (21). Spitzer, D., et al (22)found that bromocriptine and cabergoline have similar OHSS preventive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, bromocriptine is often used for OHSS prevention [22]. Spitzer et al [23] found that bromocriptine and cabergoline have similar OHSS preventive effects.…”
Section: Introductionmentioning
confidence: 99%